Performance of a Nonelectric Infant Warmer in Rwandan Health Centers - Leana May DO; Alphonse Nshimyiryo MSc; Marthe Kubwimana RN; Evrard Nahimana MD; Natalie Schoen; Ashok Gadgil PhD; Fredrick Kateera MD; Henry A. Feldman PhD; Merab Nyishime MSc; Anne Hansen MD, MPH (SAGE Publishing, 2019)
Background . Neonatal hypothermia remains a challenge in resource-limited settings. Methods . We conducted a prospective mixed-methods cohort study in rural Rwandan health centers to assess the performance of an infant warmer we designed for low-resource settings. All hypothermic infants were eligible for enrollment. Outcomes . Safety: incidence of adverse reactions. Effectiveness: attainment of euthermia, rate of temperature rise. Feasibility: correct use of warmer, signs of wear. Interviews of caregivers and nurses. Findings . Of 102 encounters, there were no adverse reactions. Of 80 encounters for hypothermia when infants on warmer for ≥1 hour, 79 achieved euthermia; 73 in ≤2 hours. Of the 80 encounters, 64 had temperature rise ≥0.5°C/h. Of the 102 encounters, there were no instances of the warmer being prepared, used, or cleaned incorrectly. Five out of the 12 warmers exhibited wear. Interview participants were predominantly positive; some found time for readiness of warmer challenging. Interpretation . The warmer performed well. It is appropriate to study in larger scale.